(untitled) (Philology, 2024)
Modern technologies are very important for modern society, they play a key role in the development of all areas of science. The relevance of the use of ICT in literature lessons lies in the fact that developing every day information technologies contribute to the effective organisation of the educational process, expand access to information (e-books, online libraries, literary databases and other Internet resources) and allow the use of interactive teaching methods, such as online discussions, quizzes, collective creation of digital projects and much more, which promotes active learning activities of students.